Survey of Nano filtration Performance for Hexavalent Chromium Removal fromWater Containing Sulfate - Gh.R Moussavi (سلامت و محیط, 2010)
"n "n "nBackgrounds and Objectives: Geological situation and/or anthropogenic contamination contain an increased concentration of ions such as hexavalent chromium as well as some other dissolved components such as sulfate in the upper of the establishedMCLs (50µg/L). In this paper, simultaneous removal of Cr (VI) and sulfate from water was investigated using nanofiltration as a promising method for reaching drinking water standards."nMaterials and Methods: For varying pressure, pH , anion and cation solution effect, Sulfate and Cr (VI) concentration which have chosen were levels found in drinking water sources (Cr=0.1- 0.5mg/L) and (SO4-2= 100-800mg/L).Experiments were performed using NaCl, Na2SO4,K2 Cr2O7and anhydrous CrCl3. 6H2O which prepared with de mineralized water on procedure detailed in standard methods. All salts were purchased from Merck Corporation with purity over 99'."nResults: The results for hexavalent chromium experiments showed that when the concentration decreases, the chromate anions were given a better retention to 4 bars (96'). But when the concentration increases, concentration polarization led to increased removal of Cr (VI) (98'). For Cr (III) the influences of the ionic strength as well as the concentrations were strongly dependant on rejection but operating pressure were found weak. In addition, with increasing total dissolved solids, perfect rejection of chromium was seen. The effect of pH showed that better retention was obtained at natural and basic pH."nConclusion: This study indicates that the nature of anions and cations, driven pressure and pH have significant effect on nano filtration operation. Research findings show that it seems nano filtration is a very good promising method of simultaneous removal of Cr (VI) and sulfate from water.